Screening local landraces of melon for resilience to salinity stress under hydroponic greenhouse conditions - Ntanasi, Theodora; Ntatsi, Georgia; Karavidas, Ioannis; Outos, G.; Maloukos, G.; Fotopoulos, Vasileios; Guillaume, M.; Causse, Mathilde A.; Clemente, M. J.; Schubert, Andrea; Galmès, Jeroni; Conesa, Miquel Àngel; et al. (My University, 2023)
Water shortage and heat driven evaporation in semi-arid climate, such as Mediterranean, that are mainly ascribed to climate change, introduced salinity as a major stress factor in vegetable crop production. Thus, the adaptation of vegetables, especially those susceptible to osmotic stress, is becoming more and more challenging to acquire sustainable cropping systems in saline environment. Unlike melon hybrids, melon landraces are less sensitive to environmental stresses and considered valuable sources of genetic characteristics for plant breeders' interest in breeding programs. This study was designed to assess the impact of salinity on several fruit quality characteristics of three melon landraces namely 'Tendra negro', 'Thrakiotiko' and 'Leyko Amyntaiou'. Both, the widely cultivated Spanish cultivar 'T111 (tipo piel de sapo)' and the commercial hybrid 'Lavigal' served as control. The experiment was carried out at the greenhouse facilities of the Laboratory of Vegetable Production at the Agricultural University of Athens. The different melon genotypes were hydroponically cultivated in an open hydroponic system with perlite as substrate, by applying a nutrient solution of 0.5 mM NaCl to the non-saline treated plants and 30 mM NaCl to the salt exposed plants. To investigate the impact of the salt stress on fruit quality, parameters such as the dry matter content, the pulp firmness, the values of color parameters L∗ a∗, b∗, hue angle and chroma and the titratable acidity were determined. The results showed that the color parameters and the pulp firmness were cultivar depended and were not affected by the salinity stress applied. Moreover, salinity stress resulted in increased dry matter content of the landrace 'Thrakiotiko', increased titratable acidity of the landrace 'Leyko Amyntaiou'. However, all tested parameters for the 'Tendra negro' landrace were not affected by the stress applied, indicating that this landrace could be a good candidate to be used in breeding programs for improving the tolerance of the commercial melon to salt stress.
Keywords: climate change; fruit quality; local cultivar; melon; pulp firmness; salt stress; soilless culture